Parenting Styles and Their Relationship to Aggressive Behavior Among Children: A Field Study - Najat Nouri Naseer; Farhat Al-Mabrouk Ali Zayed (Journal of Libyan Academy Bani Walid, 2025)
This field study aimed to explore the nature of the relationship between parenting styles and aggressive behavior among children in Libyan society, in light of the social and economic transformations the country is experiencing. The study adopted a descriptive correlational approach and employed two main instruments: a parenting styles questionnaire and an aggression behavior scale, applied to a purposive sample of 80 Libyan families. The results revealed that the democratic (guiding) style was the most prevalent parenting style among Libyan families, followed by the overprotective style, then the authoritarian style, and finally the neglectful style. The findings also indicated a generally high level of aggressive behavior among children, with expressive aggression scoring the highest levels. Furthermore, the results showed a strong and statistically significant correlation between parenting styles and aggressive behavior. The democratic style was strongly and negatively correlated with aggression, while the non-ideal styles (authoritarian, neglectful, and overprotective) were strongly and positively correlated with all forms of aggressive behavior, with the neglectful style having the greatest impact. The study also found that parents’ educational level and the family’s economic status play important roles in determining the parenting styles used. In light of these findings, the study recommended increasing parental awareness of balanced parenting methods, strengthening the role of educational institutions in providing family counseling, designing intervention programs for children, and supporting families educationally and economically to alleviate pressures that influence their parenting practices